Case report of intestinal non-rotation, heterotaxy, and polysplenia in a patient with pancreatic cancer. Issue 49 (December 2017) - Pagkratis, Spyridon; Kryeziu, Sara; Lin, Miranda; Hoque, Samah; Bucobo, Juan Carlos; Buscaglia, Jonathan M.; Georgakis, Georgios V.; Sasson, Aaron R.; Kim, Joseph
Abstract: Rationale: Heterotaxy with polysplenia is an extremely rare congenital condition resulting from abnormal arrangement of organs in the abdominal and thoracic cavities during embryologic development. When a malignancy such as pancreatic cancer develops under these conditions, surgical resection becomes particularly complex. This case report demonstrates successful pancreatic cancer resection despite the patient's complicated anatomy. Patient concerns: An 82-year-old female presented to our institution with complaints of mild right upper quadrant pain radiating to the mid-epigastric region. Diagnoses: Physical examination revealed jaundice with scleral icterus consistent with obstructive jaundice. Radiographic imaging revealed hepatic duct dilation with several anatomic anomalies including small bowel location in the right upper abdomen, cecum, and appendix in the left lower quadrant, reversed superior mesenteric artery and superior mesenteric vein positions, and right-sided duodenal-jejunal flexture as well as an entirely right-sided pancreas, and left lower pelvis with ≥6 separate splenules. These findings resulted in a diagnosis of heterotaxy syndrome with polysplenia. Interventions: Careful preoperative planning and total pancreatectomy was performed without complication. Outcomes: The patient recovered well. Pathologic examination of the pancreatic mass revealed moderately/poorly differentiated invasive pancreatic duct adenocarcinoma. The patient remains alive and well without signs of recurrent disease at the 2-year follow-up. Lessons: Given the wide range of anatomical variants observed in patients with heterotaxy syndrome, a thorough radiologic assessment is necessary before engaging in any surgical procedure. In our case, preoperative identification of the various anatomic anomalies, such as the short and vertically oriented pancreas, the porta hepatis position anterior to the duodenum, the nonrotation of the intestines and the anomalous origin of the right hepatic artery allowed us to perform a safe and uncomplicated total pancreatectomy.